(untitled) (Mustansiria Dental Journal, 2024)
The aim of the present study was to compare nickel titanium and stainless steel spreaders penetration depth and load in lateral compaction. Thirty curved mesial canals of extracted mandibular molars were used in the study. The canals were prepared using step-back technique with Gates-Glidden. Afterward the teeth were divided randomly into 2 groups. In part 1 of the study, the force required to insert each spreader to within 1 mm of the working length in an empty canal was measured . In part 2, the force required to insert each spreader to within 2 mm of the working length was measured in canal containing a master cone. ln part 3, the depth of penetration of each spreader with a master cone in place using a 1.5 kg force was measured. Using a t-test for paired samples, the results from pan 1 showed that nickel titanium spreader required high significantly less force than stainless steel s reader P<0.01 . ln part 2, a nickel titanium s reader re uired high si niticantl less force than a stainless steel spreader .As expected in part 3, a nickel titanium spreader penetrated to a significantly high depth than stainless steel spreader (P<0.0l